How to Calibrate Fiscal Rules : A Primer - Eyraud, Luc (IMF How To Notes; How-To Note ;, 2018)
This note provides guidance on how to calibrate fiscal rules, that is, how to determine the thresholds (ceiling, floor, or target) for specific fiscal aggregates constrained by rules. The note focuses, more specifically, on the calibration of the debt, balance, and expenditure rules. The note is divided into four sections. The first section discusses general principles used to calibrate rules. The second section reports international evidence on the numerical ceilings used in existing rules. The third and fourth sections provide guidance on the calibration of the debt ceiling and the operational rules (fiscal balance and expenditure rules). This is one of two guidance notes on the design of fiscal rules; the other one focuses on rule selection. The two exercises are linked: if a fiscal framework had to be built from scratch, rules would need to be selected and calibrated at the same time.